The molecular characterization of the virus and virus-line agents present in Ta Tao 5 germplasm of Prunus persica - Marini, Diana Beatriz (Clemson University, 2020)
Tesis para obtener el grado de Doctor of Philosophy Plant and Environmental Sciences, de Clemson University, diciembre 2007